Long-term outcomes and patterns of failure in orbital lymphoma treated with primary radiotherapy. Issue 5 (May 2015) - Parikh, Rahul R.; Moskowitz, Bruce K.; Maher, Elizabeth; Della Rocca, David; Della Rocca, Robert; Culliney, Bruce; Shapira, Ilan; Grossbard, Michael L.; Harrison, Louis B.; Hu, Kenneth
Abstract The purpose of this study was to evaluate the long-term outcome and patterns of failure in patients treated with primary radiotherapy (RT) for orbital lymphoma (OL). Seventy-nine patients diagnosed with stage IE OL between 1995 and 2012 were included. Fifty-nine patients (75%) had mucosa-associated lymphoid tissue lymphoma and 20 patients (25%) had follicular lymphoma subtype. The median follow-up was 49.7 months. Major tumor sites were conjunctiva (29%), orbit (47%) and lacrimal gland (24%). After treatment to a median dose of 30.6 Gy, there were a total of no local, one contralateral orbital, two regional and two distant recurrences, all outside of the treatment fields. The 10-year local relapse-free, distant metastasis-free and overall survival rates were 100%, 94.2% and 98.2%, respectively. Definitive RT to 30 Gy was shown to be highly effective for indolent OL, and this study represents one of the largest single-institution studies using primary RT for stage IE OL.